Decision Table with Inventory Turnover Ratio to Solve Operational and Strategic Issues - Surjandy Surjandy; Ita Ratnasari (Universitas Airlangga, 2018)
The research was conducted at PT CPC using qualitative research methodology. It focused on group discussion to identify problem statements and analyst selling data to make an inventory distribution model strategy. The aims are to determine whether decision table could be implemented in the current situation in PT CPC, and the combination method between decision table and inventory turnover ratio indicator can solve PT CPC problem.The results find that a simple decision table is hard to be implemented due to the complexity of the problem. However, the combination of the decision table with an indicator of inventory can be used as a solution to the problem at PT CPC.